Wounding patterns in pediatric firearm fatalities. Issue 1 (January 2023) - Roberts, Bailey; James, Douglas; Haft, Julia; Balakrishnan, Nalini; Prince, Jose; Sathya, Chethan
Highlights: Pediatric wounding patterns varied by age and intent of injury (suicide, homicide, unintentional injury). Most pediatric suicide victims had injuries to the head and were dead on scene. Children with homicide and unintentional deaths had more wounding pattern variation and far fewer died on scene. Public health strategies for firearm injuries should be tailored to pediatrics based on age, intent of firearm use, and wounding pattern. Abstract: Introduction: Pediatric firearm injury became the leading cause of death among U.S. children in 2020. Studies evaluating wounding patterns in military and mass casualty shootings have provided insights into treatment and potential salvageability in adults, however, similar studies in the pediatric population do not exist. Hence, our study aimed to analyze wounding patterns of pediatric firearm fatalities and associated demographics and characteristics, such as place of death, to better understand pediatric firearm injuries, potential salvageability, and opportunities to reduce firearm deaths among vulnerable pediatric populations. Methods: A retrospective review of the National Violent Death Reporting System from 2005-2017 was performed on patients 18 and younger. Mortalities were stratified by patient age: <12 years and 13-18 years and by intent— homicide, suicide, and unintentional. Comparative and exploratory analyses of demographics, location of death and anatomic location of wounds were performed. Results: Of 8, 527 pediatric firearm mortalities identified, 4, 728 were homicides, 3, 180 were suicides and 619 were unintentional injuries. Suicide victims were most likely to be dead on scene and >90% of suicide victims suffered head/neck injuries. For victims of homicide, younger children were more likely to die on scene (61% vs 44% p < 0.001). The pattern of injury in homicides differed for younger children compared to adolescents, with younger children with more head/neck injuries and older children more thoracic, thoracoabdominal, abdominal, and junctional injuries. In both age groups, children with extremity, abdominal and thoracoabdominal injuries were more likely to die later in the emergency department or inpatient setting. Conclusions: Wounding patterns across pediatric firearm mortalities in the U.S. vary by age and intent. The majority of pediatric firearm deaths were due to head/neck injuries. Children with homicide and unintentional deaths had more wounding pattern variation, including more injuries to the thorax and abdomen, and a much lower rate of dead-on scene than suicide victims. Our study of wounding patterns among U.S. children killed by firearms highlights the complexity of these injuries and offers opportunities for tailored public health strategies across varying vulnerable pediatric populations.